Implementing Agile Approach In Inventory Management De-velopment To Enhance Performance Of Fitness Centers - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This study aims to develop a responsive and efficient membership management application for fitness centers using the Extreme Programming (XP) Methodology. Challenges encountered in membership management at fitness centers include complex registration processes, difficulties tracking payments, and inefficient member data management. The methodology involves system requirements analysis involving stakeholders, application design and implementation using XP approaches such as short iterations and continuous testing, and trial and evaluation involving internal teams and fitness center members. The result is an application that integrates essential features such as membership management, class scheduling, payments, member progress reporting, communication, and equipment reservations. Alpha and beta testing, as well as member performance and response evaluations, indicate that this application can meet user expectations and enhance the operational efficiency of fitness centers. This research contributes to providing technological solutions that improve fitness center membership management processes with a responsive and practical approach in line with XP principles in software development.